Optimising the mechanical properties of concrete for non-structural applications through partial replacement of fine aggregates with wastewater sludge - Kobe Samuel Mojapelo; Williams Kehinde Kupolati; Everardt Andre Burger; Julius Musyoka Ndambuki; Jacques Snyman; Emmanuel Rotimi Sadiku; Idowu David Ibrahim (Scientific Reports)
Abstract This study investigated the potential of wastewater sludge (WWS) as a partial replacement for fine aggregates in non-structural concrete to optimise its mechanical properties while mitigating environmental impacts. WWS from three wastewater treatment plants (WWTPs), Mankweng, Polokwane, and Seshego, in Limpopo Province, South Africa, was used to replace sand at 0, 5, 10, 15, and 20% by weight. Scanning electron microscopy (SEM), X-ray diffraction analysis (XRD), and energy-dispersive X-ray analysis (EDX) were used to characterise the organic compositions of the sludge and sludge-based concrete. The environmental safety of the sludge-based concrete was then assessed through the Toxicity Characteristic Leaching Procedure (TCLP) at 28, 90, and 140 days, ensuring compliance with heavy metal leaching limits. The results demonstrate that at a 5% replacement level, the concrete maintained an average compressive strength of 25 MPa after 90 days, meeting general construction standards for non-structural and low load-bearing applications. The incorporation of wastewater sludge had low leachable heavy metals, with TCLP results confirming all tested metals remained below regulatory limits throughout. However, increasing WWS content beyond 10% resulted in higher porosity, reduced compressive strength, and increased water absorption, which compromise durability. The findings highlight the importance of optimising replacement levels and mix design to balance sustainability, mechanical performance, and regulatory compliance.